Electronic Structure and Optical Properties of N/Si-Codoped Anatase TiO2 Evaluated Using First Principles Calculations - Huey-Jiuan Lin; Hsuan-Chung Wu (International Journal of Photoenergy)
First principles calculations were used to evaluate the electronic structure and optical properties of N/Si-monodoped and N/Si-codoped TiO2 to further understand their photocatalytic mechanisms. In accordance with the atomic distance between N and Si dopants, this study considered three N/Si codoping configurations, in which the N dopant had a tendency to bond with the Si dopant. The calculations showed that the bandgaps of the N/Si codoping models were narrow, in the range 3.01–3.05 eV, redshifting the intrinsic absorption edge. The Si 3p orbital of N/Si-codoped TiO2 plays a key role in widening the valence band (VB), thereby increasing carrier mobility. In addition, the N-induced impurity energy level in the forbidden band appears in all three N/Si codoping models, strengthening absorption in the visible region. The bandgap narrowing, VB widening, and impurity energy levels in the forbidden band are beneficial for improving the photocatalytic activity of N/Si-codoped TiO2.